ASSOCIATION BETWEEN ALCOHOL CONSUMPTION AND BREAST CANCER DEVELOPMENT: A CASE-CONTROL STUDY - Portela, Laís Franciele Santana; Machado, César Augusto Costa; Cangussú, Renata Costa; Landeiro, Luciana Castro Garcia; Bertrand, Susanne de Andrade Blanc; Pinto, Rebecca Meireles de Oliveira (Mastology, 2017)
Objectives: To identify the association of alcohol consumption with the development of breast cancer in a patient population of Salvador, Bahia. Methods: Case-control study, conducted between December 2013 and May 2015, with 69 patients with breast ductal carcinoma and 71 controls. Sample calculation was made with 140 patients, with 5% presumed difference between groups and 10% acceptable difference. The χ2 test was used to evaluate the correlation between categorical variables, and Student’s t-test was applied to compare continuous variables. Results: From all cases, medium alcohol intake was 3.66±8.60 g/day; among controls, the average was 3.71±7.40 g/day (p=0.890). When analyzing the association between alcohol intake and breast cancer, odds ratio was 0.99 (95% confidence interval 0.524–1.890), p=0.988. For alcohol consumption greater than 10 g/day and breast cancer, odds ratio was 1.579 (95%CI 0.624–3.995), p=0.332. Conclusions: Although published data suggest an association between alcohol consumption and breast cancer, in this study there was no statistical significance between the variables assessed and the onset of this pathology.